The impact of machine perfusion of the heart on warm ischemia time and organ yield in donation after circulatory death. Issue 5 (16th February 2022) - Feizpour, Cyrus A.; Gauntt, Katrina; Patel, Madhukar S.; Carrico, Bob; Vagefi, Parsia A.; Klassen, David; MacConmara, Malcolm
Abstract : Successful normothermic machine perfusion of heart allografts (MPH) has led to rapid growth in transplantation of donation after circulatory death (DCD) heart allografts but has introduced complexity in the procurement process. This study examines the impact of MPH use in DCD procurements on warm ischemia time (WIT) and organ yield. DCD procurements from 2019 to 2020 were identified using the OPTN database. Procurements with and without the use of MPH were compared using propensity score matching. Observed to expected (O:E) yield ratios were calculated, where the expected values were obtained using the models developed by the Scientific Registry of Transplant Recipients. In total, 1237 DCD procurements met inclusion criteria (MPH: 109 and control: 1128). After PSM, no difference was found between groups in median total WIT (24.0 min vs. 24.0 min, p  = .89), but the MPH group demonstrated shorter median operative WIT (circulatory arrest to cross‐clamp; 8.7 min vs. 10.9 min, p  = .003). The overall organ yield of DCD heart donors was observed to be 33% higher than expected (O:E 1.33; 95% CI: 1.22–1.45). Observed yield of non‐heart organs was not significantly different from expected for liver, kidney, lung, and pancreas grafts. MPH use in DCD procurements does not lead to delays in WIT and does not negatively affect organ yield of other concurrently procured organs. Abstract : Machine perfusion of donation after circulatory death hearts does not increase warm ischemia time and does not reduce the yield of other organs.